Formy spędzania czasu wolnego studentów wybranych kierunków Uniwersytetu Kazimierza Wielkiego w Bydgoszczy = Forms of spending free time students of selected fields of the University of Bydgoszcz - Łachacz, Martyna; Cieślicka, Mirosława; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Martyna Łachacz, Mirosława Cieślicka, Walery Zukow. Formy spędzania czasu wolnego studentów wybranych kierunków Uniwersytetu Kazimierza Wielkiego w Bydgoszczy = Forms of spending free time students of selected fields of the University of Bydgoszcz. Journal of Education, Health and Sport. 2016;6(8):333-362. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60710 http://ojs.ukw.edu.pl/index.php/johs/article/view/3765 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. Formy spędzania czasu wolnego studentów wybranych kierunków Uniwersytetu Kazimierza Wielkiego w Bydgoszczy Forms of spending free time students of selected fields of the University of Bydgoszcz Martyna Łachacz, Mirosława Cieślicka, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Kreowanie odpowiednich nawyków wolnoczasowych jest bardzo ważnym aspektem w dzisiejszych czasach. Należy wciąż uświadamiać społeczeństwo, że aktywność fizyczna stanowi niezbędny element zachowania dobrostanu psychicznego i fizycznego człowieka. Wiele osób nadal nie rozumie, że regularna aktywność ruchowa przyczynia się do zmniejszenia ryzyka wystąpienia chorób cywilizacyjnych, na które umiera większość społeczeństwa. Dlatego ważne są badania sprawdzające jak spędzają czas wolny osoby w różnym wieku oraz czy i jakie formy rekreacji ruchowej podejmują, jakie mają podejście do aktywności fizycznej, czy są świadomi, że w ich otoczeniu są organizowane zajęcia sprzyjające zwiększeniu sprawności fizycznej oraz czy i jakie różnice występują między poszczególnymi grupami społecznymi. Badania przeprowadzono, w styczniu 2015 roku, na Uniwersytecie Kazimierza Wielkiego w Bydgoszczy. Badania przeprowadzono na studentach I, II oraz II roku administracji oraz Turystyki i Rekreacji. Zgromadzony materiał badawczy to 102 ankiety, po 17 na każdym roczniku i kierunku. W badaniu wzięło udział 74 kobiety oraz 28 mężczyzn w wieku od 19 do 25 lat. Analizując wyniki badań można wysunąć wniosek, że występują małe różnice w postrzeganiu aktywności fizycznej studentów administracji oraz turystyki i rekreacji. Studenci TiR częściej wybierają aktywność ruchową. Jak widać studenci administracji mają nieco inne priorytety lub być może wiedza na temat rekreacji ruchowej nie jest im tak często i skutecznie przekazywana jak studentom TiR. Słowa kluczowe: czas wolny, aktywność fizyczna, rekreacja ruchowa, studenci. Abstract Creating the appropriate lot of habits is a very important aspect nowadays. You should still realize a society that physical activity is an essential element in maintaining a mental or physical man. Many people still do not understand that regular physical activity helps to reduce the risk of lifestyle diseases, which the majority of the population dies. It is therefore important tests are checking how they spend their free time people of all ages and whether and what forms of recreation take what they approach to physical activity, whether they are aware that their surroundings are organized activities conducive to increasing physical fitness and whether and what differences exist between different social groups. The study was conducted in January 2015 at the University of Bydgoszcz. The study was conducted on students I, II and II, the administration and Tourism and Recreation. The accumulated research material is 102 survey, after 17 on each yearbook and direction. The study involved 74 women and 28 men aged 19 to 25 years. Analyzing the results of the research can conclude that there are small differences in the perception of physical activity student administration and tourism and recreation. Students often choose TiR physical activity. As you can see, students administration have slightly different priorities, or perhaps knowledge of physical recreation is not them so often and effectively passed on to students TiR. Key words: leisure, physical activity, physical recreation, students.